Foods of Italy - Sheen, Barbara (New York Kidhaven Press, 2006)
This book explores the foods, cooking traditions, customs, eating habits, and food sources all presented through a delectable blend of geography, daily life, culture, and history.
1 - 6
Keywords: 1. Cookery, Italian; 2. Italy - Social life and customs; 3. A Taste of Culture